Development of Brewing in Kharkov Province in the second half of the XIX century: Causes of German Breweries Monopoly. - Філатова, Ольга (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article is devoted to the study of development features of the brewing industry in Kharkiv province in the second half of the XIX century. Special attention is paid to the peculiarities of enterprises functioning created by ethnic Germans. Information on production capacity, equipment, volumes, range, and quality of manufactured products are provided. The causes of regional market monopolization by German breweries during the second half of the XIX century are investigated.